Hegel’s Concept of Action between Deflationary Approaches and The Science of Logic - Tereshchenko , Yuliia (ETHICS IN PROGRESS, 2022)
The research in this paper attempts to outline the connection between Hegel’s concept of action and the contemporary philosophy of action. Hegel’s concept of action has some features in common with the ideas of analytical philosophers, and might open unexpected integration of these different philosophical traditions, which would contribute to the development of both of them. A brief overview of ways to comprehend Hegel’s concept of action (from Taylor to Brandom) shows that the cause of ambiguous understandings of this concept lies in the complexity of Hegel’s approach. The following article highlights the tension between “deflationary” interpretations and the complexity of Hegel´s original approach. Further, by revisiting the Section “Teleology” in Hegel’s Science of Logic, the article illustrates how deflationary interpretations of human action can be improved, so that they are topical for both contemporary practical philosophy and the philosophy of action, beyond the unnecessary split between analytical vs. continental philosophy. Such concepts as “purpose” and “mediation” become crucial, as they have sociological and normative extensions in Hegel’s Philosophy of Right, as discussed in the last Section of this article.